(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
This study aims to analyze the relative concentration (C/C0) data to investigates the solute transport breakthrough. The modeling approaches considered were the Convection-Dispersion Equation (CDE), Two-Region Model (TRM), and Continuous Time Random Walk (CTRW). It was found that higher values of determination coefficient (R2) and lower values of root mean square error (RMSE) concerning the fits of CDE and TRM and CTRW. In this study the CXTFIT2.1 software and to carry on the simulation analysis of CDE and TRM. For the CTRW simulation of the breakthrough curve, we used the CTRW Matlab Toolbox v.3.1. It is figured that, in the comparison of CDE, TRM, and CTRW models analysis of the relative concentration in low-permeability media; we tend to use CTRW to describe the transport behavior well because there are prevailing Fickian and non-Fickian transport. One dimensional CTRW results yielded a set of five dominant parameters (υψ, Dψ, β, t1, and t2), indicated that a transport regime that was consistently Fickian in the breakthrough curve (BTC). The CTRW gives better fitting results to the BTCs when β has an increasing pattern towards 2.00.